Improving Student Learning Outcomes by Implementing Synectic Learning Strategies - Elisabeth Sitepu (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to improve student learning outcomes by using synectic learning strategies at Jambi Medan Private High School. The population is all class XI high school students consisting of 2 classes. Samples were taken randomly in 2 classes consisting of an experimental class and a control class. The data observed were student learning outcomes, which were collected through a multiple-choice test of 25 questions consisting of 5 answer options, which had been tested for validity, reliability, level of difficulty and differentiating power of the test. The data obtained were analyzed using the t test, where the normality and homogeneity of the data had previously been tested. The experimental class learning outcomes averaged pretest (28.42 ± 6.71) and average posttest (73.51 ± 5.64) with an increase in Gain learning outcomes of 67% while the control class learning outcomes averaged pretest (21 .62 ± 6.48) and the posttest average (69.53 ± 5.96) with an increase in Gain learning outcomes of 61%. Hypothesis testing was carried out at a significance level of α = 0.05 using a one-sided t-test, namely the right side where tcount > ttable (2.85 > 1.67), which means Ho was rejected and Ha was accepted. By looking at the results of this research, it can be concluded that the learning outcomes of students who are treated through the application of Synectic learning strategies are higher than those using conventional teaching